2017
DOI: 10.1093/gbe/evx174
|View full text |Cite
|
Sign up to set email alerts
|

Dominance and Sexual Dimorphism Pervade the Salix purpurea L. Transcriptome

Abstract: The heritability of gene expression is critical in understanding heterosis and is dependent on allele-specific regulation by local and remote factors in the genome. We used RNA-Seq to test whether variation in gene expression among F1 and F2 intraspecific Salix purpurea progeny is attributable to cis- and trans-regulatory divergence. We assessed the mode of inheritance based on gene expression levels and allele-specific expression for F1 and F2 intraspecific progeny in two distinct tissue types: shoot tip and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 85 publications
1
38
0
Order By: Relevance
“…This is quite different from the closely related genus Populus where sex-determining regions consistently occur on chromosome 19, with most species showing male heterogamety [23,24]. Previously, we reported that the SDR occupies a large portion of the W chromosome in S. purpurea with suppressed recombination extending over~5 Mb [20,25]. This is substantially larger than the SDR in P. trichocarpa and P. balsamifera, which appears to be approximately 100 kb in size [24,26].…”
Section: Introductionmentioning
confidence: 64%
“…This is quite different from the closely related genus Populus where sex-determining regions consistently occur on chromosome 19, with most species showing male heterogamety [23,24]. Previously, we reported that the SDR occupies a large portion of the W chromosome in S. purpurea with suppressed recombination extending over~5 Mb [20,25]. This is substantially larger than the SDR in P. trichocarpa and P. balsamifera, which appears to be approximately 100 kb in size [24,26].…”
Section: Introductionmentioning
confidence: 64%
“…SA effects are plausible [ 19 ], including in animals in which sexual selection occurs, or similar differences in investment in attractiveness to pollinators by male plants versus females [ 20 ]. Levels of expression of many genes may differ in the two sexes of animals [ 21 ] and plants [ 22 , 23 , 24 ], supporting the idea that the two sexes have different evolutionary optima for expression. However, SA polymorphisms establish only under restricted conditions [ 25 ], and empirical tests are needed to find out whether such polymorphisms indeed occur and are maintained long enough to cause the effects proposed in theoretical models.…”
Section: Evolution Of Separate Sexes and Suppressed Recombination mentioning
confidence: 99%
“…This is quite different from the closely-related genus Populus where sex determining regions consistently occur on chromosome 19, with most species showing male heterogamety [21, 22]. Previously, we reported that the SDR occupies a large portion of the W chromosome in S. purpurea , because a large region on Chr15 shows lack of recombination and a large number of female-biased alleles [18, 23]. This is different from the small SDR observed in P. trichocarpa and P. balsamifera [22, 24].…”
Section: Introductionmentioning
confidence: 96%